Validation of a rapid biomarker assay for lung cancer using the IntelliPlex panel - Sandra Satie Koide; Breno Jeha Araújo; Juliana Doblas Massaro; Renata de Godoy e Silva; Rodrigo Dienstmann; Fernanda Christtanini Koyama Ribeiro (Scientific Reports)
Abstract A large proportion of non-small-cell lung cancer (NSCLC) patients harbor clinically actionable genomic alterations, detected in general by broad Next-Generation Sequencing (NGS) panels, since it is the gold standard test and strongly recommended by different societies. However, high failure rates due to preanalytical factors and long turnaround times are still hindering rapid treatment decision taking in the real-world setting. The objective of this study was to validate the IntelliPlex Lung Cancer Panel by πCODE Technology for biomarker detection using clinical specimens compared to NGS as the gold standard methodology. A total of fifty-eight (58) Formalin-Fixed Paraffin-Embedded tissue (FFPE) samples from fifty-three (53) patients diagnosed with advanced lung adenocarcinoma and 2 reference controls were used. Overall, the test presented 97,73% sensitivity, 100% specificity and 98,15% accuracy. The IntelliPlex Lung Cancer Panel DNA presented 98% agreement, and the IntelliPlex Lung Cancer Panel RNA presented 100% agreement between the results obtained from the CGP NGS methodology. The IntelliPlex Lung Cancer Panel by πCODE Technology demonstrates high specificity and sensitivity for use in clinical laboratories to routine detection for actionable mutations and fusions in NSCLC tumor samples, with high potential to become an alternative to broad NGS panels according to pre-analytical factors.